Social trading, correlated retail investing and non-fundamental speculation - David Russ (Deutsche Bundesbank, 2025)
This paper shows that, in a setup 'a la Kyle (1985), correlated retail trading opens up new profit opportunities for professional investors at the expense of retail investors. Additionally, it demonstrates that market quality can benefit through higher market liquidity and higher price efficiency. Our results lend support to concerns that social trading via Finfluencers and stock message boards harms rather than benefits retail investors.
Keywords: G12; G14; 330; social trading; noise trading; non-fundamental information; strategic trading